Variety specific integrated fruit production development in order to optimize inner content values - Kállay, E.; Ficzek, G.; Andor, D.; Stéger-Máté, M.; Boronkay, G.; Kirilla, Z.; Bujdosó, G.; Végvári, Gy.; Tóth, M. (International Journal of Horticultural Science, 2010)
In this paper we introduce our results of three years (2007-2009) investigatio ns carried out in the framework of "Research and development in foodstaff chain" - project of Regional University Knowledge Center by the members of Corvi nus U niversity of Budapest - Department of Pomology and. Research Institute for Fru it growing and Ornamentals.  Budapest-Erd. The main objectives of the project were the followings: submi ssion of sour cherry candidate suitable for industrial process for state approval; determination of physica l parameter and inner content value changes of sour cherry varieties duri ng ripening; evaluation of health care attributes of sour cherry fruit; ripen ing process description by the colour and the force required to pick fruits of sour cherry. We stated that the optimal begi nning and period of the harvest can be determined wi th the fruit removal force. In this period the fruit growth stops. ju iciness rat io does not change. refractions are approximately equal.acidic content turns to decreasing trend.However the proportion of anthocyan in and polypheno l can still increase. Fruits harvested in this period fulfil a wide range of industrial process opportunities. 'Erdi jubileum ·and candidate IV-3/48 according to their inner content values arc suitable for high quality products (containing real fruit material in high proportion).